Nitriding, oxidation and carburization of titanium and steels in non-self maintained gaseous discharge - Timoshenko, A.I.; Taran, V.S.; Misiruk, I.O. (Вопросы атомной науки и техники, 2012)
The samples of stainless steel (SS), high speed steel (HSS) and titanium (Ti) were exposed to fluxes of ions N⁺, O⁺, and CmHn⁺ which have been ejected from hollow anode into hollow cathode (vacuum chamber). It has been found that the oxidation of Ti is going faster than the nitriding does. The surface microhardness of samples treated by fluxes of ions in non-self maintained gaseous discharge grows from 1.5 for HSS (except the carburization) to 6 times for Ti and SS. Образцы из нержавеющей стали (SS), быстрорежущей стали (HSS) и титана (Ti) подвергались воздействию потоков ионов N⁺, O⁺, и CmHn⁺, которые эжектировались из полого анода в полый катод (вакуумную камеру). Найдено, что процесс оксидирования титана идет с большей скоростью, чем азотирование. Поверхностная микротвердость образцов, обработанных потоками ионов в несамостоятельном газовом разряде, увеличивается от 1,5 для быстрорежущей стали (за исключением карбидизации) до 6 раз для титана и нержавеющей стали. Зразки з нержавіючої сталі (SS), швидкоріжучої сталі (HSS) і титану (Ti) були піддані дії потоків іонів N⁺, O⁺ і CmHn⁺, які ежектувалися з порожнистого анода в порожнистий катод (вакуумну камеру). Знайдено, що процес оксидування титану йде з більшою швидкістю, ніж азотування. Поверхнева мікротвердість зразків, оброблених потоками іонів в несамостійному газовому розряді, збільшується від 1,5 для швидкоріжучої сталі (за винятком карбідизації) до 6 разів для титану і нержавіючої сталі.